PENINGKATAN KETERAMPILAN BERPIKIR KRITIS DAN PEMAHAMAN KONSEP TRIGONOMETRI MELALUI PENERAPAN PROBLEM BASED LEARNING PADA SISWA SMA NEGERI 1 PANDAAN - Siti Fatimah (Universitas Tribhuwana Tunggadewi, 2020)
The purpose is to increase critical thinking skills and conceptual understanding of mathematical trigonometric equations through problem-based learning model. The type of money research used is PTK with the subjects of all class XI MIA 3 students of SMA Negeri 1 Pandaan in the 2019/2019 academic year, totaling 35 students. The results showed that after the first cycle was implemented, 73.06% of students who think critically with sufficient qualifications were obtained, then increased in the second cycle with a result of 81.66%. The students’ conceptual understanding also increased where in the first cycle of 35 students only 6 students (17.14%), then increased in cycle II to 19 students (54.29%) with good qualification. It showed that the problem-based learning model can actually improve critical thinking skills and conceptual understanding because students are actively involved in collecting, studying, and discussing math facts related to the subject matter of trigonometric equations compared to before.